English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

a. y= -3(x+2)^2+7
b. y= (x-2)^2+7
c. y= -12(x+2)^2-7
d. y= -2(x-2)^2+7

2007-01-27 11:50:11 · 4 answers · asked by lana l 1 in Science & Mathematics Mathematics

4 answers

a. y= -3(x+2)^2+7

2007-01-27 11:59:11 · answer #1 · answered by Northstar 7 · 0 0

a) y=-3(x+2)^2+7

2007-01-27 12:01:06 · answer #2 · answered by jc_nyc01 2 · 0 0

If it opens down, as x becomes a very large positive or negative number, y should be a large negative number.

In a quadratic, with large positive or negative x, the x^2 term will always dominate.
So we look for equations with
y = minus something x^2

a, c, and d fit the bill. b can be eliminated.

now plug in x=-2 and calculate y for each of a, c, and d till we find a y = 7.

for a, y = -3(-2 +2)^2 + 7 = (-3 * 0) + 7 which is what we want.

The answer is a.

2007-01-27 12:02:15 · answer #3 · answered by astatine 5 · 0 0

y= -(x+2)^2 +7

2007-01-27 11:55:18 · answer #4 · answered by davidosterberg1 6 · 0 1

fedest.com, questions and answers